Effects of Plant Drugs on Lipid Peroxidation in Irradia ted Cells Onion Seeds - MAMEDLI, SEVIL A. (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
It is shown that seed treatment with herbal preparations before irradiation reduced the level of lipid peroxidation in the cells of Allium cepa.